Organic Crop Production – Ambitions and Limitations
DOI: 10.1007/978-1-4020-9316-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Use Efficiency and Leaching of Nutrients in Organic and Conventional Cropping Systems in Sweden

Abstract: In the past few years, organic farming has been proposed as a possible way of reducing N leaching from agricultural soils and improving the use efficiency of plant nutrients. This is, to a large extent, considered to be attributed to the fact that synthetic fertilisers are not allowed in such systems and the N inputs mainly originate in various types of organic manures. In this overview, results from a number of Swedish field studies are presented in which crop yields, nutrient-use efficiencies and leaching in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Our research shows that water percolation together with nutrient leaching is reduced with increasing yield . Similarly to findings by Bergström et al (2008) this result demonstrates that N leaching is not lower when using organic fertilizers compared to mineral fertilizers. Several previous studies (Hansen et al, 2000;Knudsen et al, 2006) have found that N leaching was lower in organic systems and the reason for it was lower N input.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Our research shows that water percolation together with nutrient leaching is reduced with increasing yield . Similarly to findings by Bergström et al (2008) this result demonstrates that N leaching is not lower when using organic fertilizers compared to mineral fertilizers. Several previous studies (Hansen et al, 2000;Knudsen et al, 2006) have found that N leaching was lower in organic systems and the reason for it was lower N input.…”
Section: Resultssupporting
confidence: 82%
“…Advanced use of fertilizers has resulted in significantly increased agricultural productivity, but simultaneously in a higher environmental pressure (Mondelaers et al, 2009), of which contamination of surface and groundwater by plant nutrients is among the most serious Bergström et al, 2008;Gali et al, 2012). Nutrient leaching is considered the most problematic in regions where precipitation exceeds evaporation considerably.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Swedish studies, Bergström et al concluded that organic sources of nitrogen leached more than conventional fertilizers. They attributed this to the fact that the manures and legume cover crops released the most nutrients during fallow periods or at times that did not sync with nitrogen demand of the crop [50].…”
Section: Challenges In Organic Agriculturementioning
confidence: 99%
“…Together, there is evidence that the overall C balance of soil, provided similar amounts of manure are available, is not systematically different between, on the one hand, mixed (organic) systems where manure is applied within single farms or, on the other hand, specialized conventional farming that selectively spreads high rates of manure but only on a fraction of the conventional land. But it should be noted that excessive organic fertilization, be it in conventional or organic systems, may cause substantial environmental problems, for example nutrient leaching (Bergström et al 2008), which needs to be tackled by sustainable management practices.…”
Section: Management and Greenhouse Gases In Agriculturementioning
confidence: 99%